Studi Pemilihan Moda Angkutan Barang Kapal Kayu dan Kapal Fery Rute Kota Tarakan-Kabupaten Tana Tidung - Muhammad Djaya Bakri; Septa Utami Dewi; Iif Ahmad Syarif (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Tana Tidung Regency as a new autonomous region in North Kalimantan in 2007 resulted in increased interactions between regions in support of the supply of food, and other social needs. Tarakan City is an essential region supporting the Tana Tidung Regency. Currently, public the primary transportation from the Tarakan-Tana Tidung is served by two modes of transportation; Ferry Boats and Wooden Boats. Researchers conducted a study to identify the trends and variables that affect the choice of Tarakan-Tana Tidung freight routes to enhance the performance of primary public transportation. Study used variable freight costs per coli, travel time, the timetable for departure, service convenience, and travel time to the Port of Tengkayu 1 or Juata Ferry Port adapted from the study of transportation mode selection by travelling persons. The survey, in the form of a questionnaire to 170 respondents, used the stated preference method and was conducted with multiple regression analysis to obtain the quantitative relationship between a collection of research variables and respondents to obtain utility and probability by modelling the binomial logit. The research results showed that the discrepancy between the Ferry Boats and Wooden Boats was in balance, with 65% of the patrons choosing the Wooden Boat to support the freight activities. All research variables have been influential in the choice of goods transport mode in the most dominant order, namely goods transportation cost per coli variables, travel time, the timetable for departure, service convenience, and travel time to port.